Building an agroecological model to understand the effects of agrochemical subsidies on farmer decisions - Bernal Hoyo, David; Giraldo, Omar Felipe; Rosset, Peter M. [UNESP]; López Corona, Oliver; Perez Cassarino, Julian; Nautiyal, Sunil (Taylor & Francis, 2022)
We present a simple simulation model whose purpose is to explore qualitatively and heuristically the effects that agrochemical subsidies could have on the type of decisions farmers make about their plots (keeping other variables fixed). We use elements of Chayanovian thinking and ecological complexity as a basis, considering that this decision is made by families with heterogeneous preferences in a context with a dynamic that, on the one hand, is non-linear for ecological cycles, and, on the other hand, is chaotic in terms of the interaction with the market. The model describes the relationship between the ecological-productive potential or capacity of a plot and the total production, as well as the effect of management (agroecological or agrochemical) on the ecological capacity. We explore the effect of agrochemical subsidies on this decision and discuss the consequences of these public policy instruments on the lives of farming families. The model shows that by using agrochemicals, both the economy and the ecological balance of the plot enter an unstable pattern with harmful long-term consequences, as there could be a significant reduction in household savings. The same effect is observed on production, since the ecological capacity tends to decrease throughout the simulation.
Keywords: Choice dynamics; fragile system; modeling; peasant; rationale; subsidies